The Reuven Fahn Collection - Govrin, Nurit (Karaite Archives, 2014)
The article, divided into five chapters, is devoted to the corpus of works by the Hebrew writer Reuven Fahn (1878–1939?) about the Karaites. The works consist of both research and literary writings. The article emphasizes the fact that Reuven Fahn was the only author who wrote stories about the lives of the Karaites in Hebrew. In the first chapter, parts of his life are depicted, emphasizing the period when he lived in the town of Halicz. The second describes briefly the variety of research and literary works he produced. The third deals with his approach as a religious Jew to research on the Karaites. The fourth studies his stories about various characters in the Karaite community and their customs. The stories demonstrate Reuven Fahn’s close familiarity with the Karaites, the compassion he felt toward them, as well as his criticism of them. The fifth is devoted to a description of seven Karaite legends that he personally heard from them and then put into writing in Hebrew. To finalize the picture, the history of the Karaites in WWII is briefly mentioned, as well as the immigration of part of the community to Israel in the 1950s. A list of selected works by Reuven Fahn concerning the Karaites is included in the article.